From archaeological data to collective identity in the present: the case of students in the districts of Supe Puerto and Paramonga, Barranca Peru - Postigo Echaiz, Wilmer Eduardo (2022)
This article develops a comparative study that exposes the relationship between archaeological interventions in the districts of Supe Puerto and Paramonga, belonging to the province of Barranca, department of Lima, with the conformation of identity in their secondary school student groups. In order to understand this relationship, semi-structured interviews have been carried out with students, a review of archaeological interventions in general, and a visit to the most representative archaeological sites in each district. The results show a relative difference in the identity conformation of both student groups, which is understood by the current condition of the archaeological sites and the specific social framework that the archaeological practice builds with them.